Estrogen receptor beta (ESR2) gene polymorphism and susceptibility to dementia - Ulhaq, Zulvikar Syambani; Garcia, Cristian Peinado (Acta neurologica Belgica, 2021)
Strong evidence supports the involvement of sex steroid hormones in the development and progression of dementia. Attention has been largely focused on the association between genetic variants of estrogen receptor alpha (ERα , ESR1 ) with dementia, although several studies indicate that ERβ is predominantly expressed in the brain. Interestingly, however, a limited number of studies evaluate the role of ERβ ( ESR2 ) in dementia. Therefore, a meta-analysis was conducted to clarify the association between ESR2 genetic polymorphisms and the risk of dementia. All the relevant studies evaluating ESR2 genetic polymorphisms and dementia were identified through online databases. In total, 14 studies including 20,609 subjects were analyzed. Collectively, it was found that a combined data set of ESR2 polymorphisms was not associated with dementia risk. Interestingly, ESR2 rs4986938 polymorphism is significantly associated with dementia in the Asian population (OR = 0.73, 95% CI 0.59–0.91, P = 0.006). The carrier of A allele in rs4986938 exhibits a protective effect against dementia (A vs. G, OR = 0.6633, P = 0.012; AA + GA vs. GG, OR = 0.6499, P = 0.014; GA vs. AA + GG, OR = 0.6672, P = 0.025; GA vs. GG, OR = 0.6617, P = 0.022). In conclusion, our study suggests that ESR2 genetic polymorphisms are not significantly associated with dementia risk. ESR2 rs4986938 may have potential as a genetic marker for dementia in the Asian population. However, further studies need to verify this conclusion.